When Does the Introduction of a New Currency Improve Welfare? - Max Fuchs; Jochen Michaelis (Philipps-University Marburg, School of Business and Economics, 2021)
In recent years, cryptocurrencies such as Bitcoin have emerged, in upcoming years, corporate currencies such as Libra (Diem) and central bank digital currencies will emerge even in low-inflation developed economies. Using the dual currency search model of Kiyotaki and Wright (1993), we show how the introduction of a supplement to traditional money affects average utility. The room for a welfare improvement depends on differences in returns and costs, but, in particular, on the fraction of cash traders who will be replaced by digital money traders.
Keywords: E41; E42; E51; 330; digital money; dual currency regime; welfare comparison